Research on horizontal multi-step cavity construction for salt cavern gas storage based on experiments - Jiasong CHEN; Xuefeng BAI; Guijiu WANG; Lianbin ZHAO; Jun LU; Lilin FAN; Haosheng LIU; Luokun XIAO (You-qi chuyun)
ObjectiveGiven that most salt rock strata in China consist of thin-layered salt formations, conventional single-well and single-cavity construction technologies are no longer adequate for the efficient construction of large-size salt cavities. In this context, the application of horizontal multi-step cavity-building technology for salt cavern gas storage can enhance the construction of salt cavities with expanded volumes in salt rock strata of limited thickness. MethodsThis study explored the influence of key parameters on the final shapes of cavities created through the horizontal multi-step cavity-building approach and analyzed both the cavity shape and the construction process from an engineering perspective, thus presenting recommended values for these key parameters. A physical simulation experimental setup was designed to examine cavity expansion patterns during horizontal multi-step cavity construction. Subsequent experiments incorporated various cavity-building parameters to generate horizontal cavities of different shapes. Finally, 3D scanning technology was employed to create complete 3D cavity models based on the cavities obtained from the experiments through mirroring operations. ResultsThe following results were derived from analyzing these 3D cavity models corresponding to various cavity-building parameters. For cavities with equal volumes, variations in water injection flow rates had a significant influence on their height, length, and maximum width. Tubing withdrawal distances had a major impact on the shape of the cavity roofs, while their effect on the overall size of the cavities was relatively minor. Additionally, the air cushion used during cavity construction to protect the roofs resulted in “flat top” shapes, which not only affected the stability of the cavities but also increased the economic costs for cavity construction. ConclusionWater injection rates ranging from 160 m3/h to 240 m3/h are considered rational for horizontal multi-step cavity building. It is recommended to use small tubing withdrawal distances. Additionally, continuous injection of dissolution inhibitors during construction for cavity roof protection is not advised. The research results offer valuable references and guidance for shape design and process parameter optimization of cavities using the horizontal multi-step construction approach for salt cavern gas storage.